A woman's empire : Russian women and imperial expansion in Asia - Hokanson, Katya (University of Toronto Press, 2023)
"A Woman's Empire explores a new dimension of Russian imperialism: women actively engaged in the process of late imperial expansion. The book investigates how women writers, travellers, and scientists who journeyed to and beyond Central Asia participated in Russia's "civilizing" and colonizing mission, utilizing newly found educational opportunities while navigating powerful discourses of femininity as well as male-dominated science. Katya Hokanson shows how these Russian women resisted domestic roles in a variety of ways. The women writers include a governor general's wife, a fiction writer who lived in Turkestan, and a famous Theosophist, among others. They make clear the perspectives of the ruling class and outline the special role of women as describers and recorders of information about local women, and as builders of "civilized" colonial Russian society with its attendant performances and social events. Although the bulk of their writings, drawings, and photography is primarily noteworthy for its cultural and historical value, A Woman's Empire demonstrates how they also add dimension and detail to the story of Russian imperial expansion and illuminates how women encountered, imagined, and depicted Russia's imperial Other during this period."--